2014
DOI: 10.1007/s11481-014-9521-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrin/Chemokine Receptor Interactions in the Pathogenesis of Experimental Autoimmune Encephalomyelitis

Abstract: Excessive infiltration of leukocytes and the elaboration of inflammatory cytokines are believed to be responsible for the observed damage to neurons and oligodendrocytes during multiple sclerosis (MS). Blocking adhesion molecules or preventing the effects of chemotactic mediators such as chemokines can be exploited to prevent immune cell recruitment to inflamed tissues. An anti-α4 integrin antibody (anti-VLA-4mAb/natalizumab (Tysabri®)) has been used as a treatment for MS and reduces leukocyte influx into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Our recent studies showed that SDF-1/CXCL12, synthesized by cells in the inflamed white matter, can induce the migration of transplanted OPCs to demyelinated white matter during EAE (Banisadr et al 2011). The up-regulation of CXCR7 during demyelination, at the peak of EAE, and it’s colocalization by OPCs arguably suggests that CXCR7 can facilitate the migration of OPCs to sites of pathology, via directed expression of SDF-1/CXCL12 on the surface of astrocytes (Banisadr et al 2014) and CNS endothelial cells, therefore, promote myelin repair. In a viral model of demyelination, CXCR4 signaling has been known indispensable for OPC proliferation and enhanced remyelination (Carbajal et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies showed that SDF-1/CXCL12, synthesized by cells in the inflamed white matter, can induce the migration of transplanted OPCs to demyelinated white matter during EAE (Banisadr et al 2011). The up-regulation of CXCR7 during demyelination, at the peak of EAE, and it’s colocalization by OPCs arguably suggests that CXCR7 can facilitate the migration of OPCs to sites of pathology, via directed expression of SDF-1/CXCL12 on the surface of astrocytes (Banisadr et al 2014) and CNS endothelial cells, therefore, promote myelin repair. In a viral model of demyelination, CXCR4 signaling has been known indispensable for OPC proliferation and enhanced remyelination (Carbajal et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NZ is a humanized monoclonal IgG4 antibody against the alpha-4 subunit of very late antigen-4 (VLA4) of α4β1 and α4β7 integrins [280] that are located on the plasma membrane of lymphocytes and monocytes. NZ is effective in RRMS patients and mainly prevents the infiltration of leukocytes into the MS brain [281], but also more specific effects on immune cells and hematopoietic populations in the CNS have been described [282]. Furthermore, NZ has important additional effects on the MS-affected CNS, including a reduction of oxidative stress and LPS-binding protein (LBP) levels [283], as wells as CSF levels of markers for intrathecal inflammation, axonal damage and demyelination [29].…”
Section: Molecular Effects Of Nzmentioning
confidence: 99%
“…The most significantly enriched functions are related to immune cell trafficking and adhesion. Specifically, the regulatory network including CXCR4, a master regulator having a known role as a stimulator of T‐ and B‐cell proliferation and migration through the endothelium . CXCR4 connects to the downstream CD6 gene encoding the SRCR domain and binding site for activated cell adhesion molecules, and further continues the process of T‐cell activation.…”
Section: Discussionmentioning
confidence: 99%